If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -5 = 15x + 3 Reorder the terms: -5 + 10x = 15x + 3 Reorder the terms: -5 + 10x = 3 + 15x Solving -5 + 10x = 3 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -5 + 10x + -15x = 3 + 15x + -15x Combine like terms: 10x + -15x = -5x -5 + -5x = 3 + 15x + -15x Combine like terms: 15x + -15x = 0 -5 + -5x = 3 + 0 -5 + -5x = 3 Add '5' to each side of the equation. -5 + 5 + -5x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + -5x = 3 + 5 -5x = 3 + 5 Combine like terms: 3 + 5 = 8 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6
| 9(6a-7)= | | 4(n+3)-2n=0 | | 4(4x+2)=-16x-8 | | 4n-3=234 | | 0.5k-4=6+2x | | x+23+x+153=170 | | -4(7x+3)=-28x-12 | | -29+3x=25-24x | | -13+x=10 | | -2(1-4v)+3=-4+8v | | 10x+15+27=14x+2 | | 27+5n=-4n+36 | | 5+5x-3x=9 | | -9+12=7x+28 | | P=36000-.2Q | | 2x-12=13-3x | | 10-3(x+3)=6x+10 | | 6-3-7h=11 | | 12x-4=46 | | 9b^3+6b^2=0 | | 2x+2-3x=7 | | 6-8x=-2-7x | | 1.4q-4.2-0.6q=-0.2q-1.6 | | 6.5-1.5(x-4)+4X=10.25 | | 0.6x^2-3.6x=0 | | -7a+3(4a+5)=5a+12 | | 4+2(5x-3)=-32 | | 2x+8(x+6)=108 | | X+1(2x+4)=84 | | 2000=10x+20y | | 3a+2-5a=-11 | | 7t-8t+4=5+-2 |